Perancangan Sistem Customer Relationship Management (CRM) Berbasis Web pada Senyaman Resto & Coffee - Rahim, Muhamad Aulia; M, Mardison; Jamhur, Annisak; Rani, Larissa Navia (Universitas Putra Indonesia YPTK Padang, 2024)
Marketing or promotional activities that are still less effective are a business obstacle, especially at Senyaman Resto & Coffee. This can be seen from the large amount of sales transaction data, sales transaction data is still recorded in books and records. Based on this, this research aims to design a Customer Relationship Management (CRM) system to increase promotional activities and improve services to Senyaman Resto & Coffee consumers. This CRM system design was built using PHP and MySql programming. CRM system design also adopts design tools using Unified Modeling Language (UML). Based on performance testing of the CRM system that has been designed, it appears that the system can provide features for creating sales and customer reports. These results had quite an impact on sales data processing which was built better than before. The contribution of this research also provides efficiency in the promotion and sales management processes that occur at Senyaman Resto & Coffee